Analisis Penggunaan Afiksasi dalam Teks Permohonan Maaf Julia Prastini â€œJuleâ€ Via Instagram Story - Dani Ardian Syach; Fahrull Maullana; Muhammad Khairul Ismi; Eva Dwi Kurniawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This analysis aims to describe the types of affixation that exist in Julia Prastini's (Jule) apology text. The approach used is a qualitative quantitative approach. Classification data collection procedures using tables. This analysis data was taken from the apology text by Julia Prastini via Instagram story. From the text of this apology, several affixations were found. The affixations found include (1) prefixes namely me-, men-, meng-, meny-, be-, ber-, ter-, ke-, se- (2) suffixes namely -an, -nya, and (3) confixes namely meng-…-kan, meny-...-kan, men-...-kan, ke-…-an, mem-…-i, meny-...-i, pe-…-an, per-…-an. Based on the analysis of the use of affixation in apology texts conveyed through social media, it can be concluded that the affixation process plays an important role in constructing meaning and delivering messages in digital discourse. The affixations identified include prefixes, suffixes, and circumfixes, which function not only as word-forming elements but also as means to express actions, states, emphasis, and the writer’s sense of responsibility. This indicates that the writer’s choice of morphological forms is closely related to the need for polite, clear, and balanced interpersonal communication.